2015
DOI: 10.2174/1568009615666150629132157
|View full text |Cite
|
Sign up to set email alerts
|

The Anthelmintic Drug Niclosamide Inhibits the Proliferative Activity of Human Osteosarcoma Cells by Targeting Multiple Signal Pathways

Abstract: Osteosarcoma (OS) is the most common primary malignant tumor of bone with a high propensity for lung metastasis. Despite significant advances in surgical techniques and chemotherapeutic regimens over the past few decades, there has been minimal improvement in OS patient survival. There is an urgent need to identify novel antitumor agents to treat human OS. Repurposing the clinically-used drugs represents a rapid and effective approach to the development of new anticancer agents. The anthelmintic drug niclosami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 81 publications
1
77
0
Order By: Relevance
“…Other anticancer drugs, including fluorouracil and niclosamide, have been reported to directly downregulate c-Myc expression in human colon cancer KM12C cells and human osteosarcoma cells, respectively (24,25). PTX treatment of HT29-4D colon carcinoma cells, HL-60 promyelocytic leukemic cells and ovarian cancer cells has been suggested to indirectly downregulate c-Myc expression (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Other anticancer drugs, including fluorouracil and niclosamide, have been reported to directly downregulate c-Myc expression in human colon cancer KM12C cells and human osteosarcoma cells, respectively (24,25). PTX treatment of HT29-4D colon carcinoma cells, HL-60 promyelocytic leukemic cells and ovarian cancer cells has been suggested to indirectly downregulate c-Myc expression (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…293pTP cells were derived from HEK-293 cells and overexpression of human Ad5 pTP gene as previously characterized [50]. The cell lines are maintained in Dulbecco's Modified Eagle Medium (DMEM) supplemented with 10% fetal bovine serum (FBS, Gemini Bio-Products, West Sacramento, CA), containing 100 U/ml penicillin and 100 mg/ml streptomycin, at 37°C in 5% CO 2 as described [51-53]. Unless indicated otherwise, all other reagents were purchased from Sigma-Aldrich (St. Louis, MO) or Thermo-Fisher Scientific (Waltham, MA).…”
Section: Methodsmentioning
confidence: 99%
“…It was, recently, reported that the antihelmintic drug niclosamide has anticancer potential in humans: it inhibits cell migration and wound closure and induces apoptosis and inhibits cell-cycle progression in BOS cells. Niclosamide is said to significantly inhibit the transcription factors E2F1, AP1, and c-MYC-responsive reporters, and it mildly inhibits the HIF1α, TCF/LEF, CREB, NFĸB, SMAD/TGFβ, and RBPJ/NOTCH pathway reporters (35). This further underscores the significant role of transcription factors in the pathogenesis of BOS.…”
Section: Transcription Factors In Bosmentioning
confidence: 92%